Autoinductive Effects in Zinc‐Catalyzed Alkylations of Benzaldehyde Mediated by Simple Chiral β‐Amino Alcohol Ligands - Joseph El Khoury; Thibault Thierry; Yannick Geiger; Stéphane Bellemin‐Laponnaz (ChemistryEurope)
The first report on enantioselective zinc‐catalyzed aldehyde alkylation mediated by a chiral auxiliary has been revisited in the context of recent advances in the field. The enantioselectivity of the alcohol formed as a function of the progress of the reaction has been studied with four different amino alcohols. During the course of the reaction, the enantiomeric ratio, in which the product is formed, is inverted, giving rise to enantiodivergence, a phenomenon that is also dependent on the catalyst loading. By combining these results with studies on nonlinear effects as well as other mechanistic studies, a model that accounts for the enantiodivergence is derived. It turns out that it is a case of catalytic autoinduction in which an active species with better enantioselectivity than the native catalyst is generated.